Quality Functions Modeling of Industrial Enterprises Products - Gumerov, Anvar V.; Biktemirova, Milyausha K.; Babushkin, Vitalii Ðœ.; Nuryyakhmetova, Svetlana M.; Moiseev, Roman E.; Nikolaeva, Anna B.; Kharisova, Regina R.; Rukomoinikova, Vera P. (International Review of Management and Marketing, 2016)
One of the integral aspects of the quality management systems of industrial enterprises is the requirement of a continuous positive development of all its processes. In this regard, it is necessary to implement the principle of "continuous improvement" and in terms of products produced by the enterprise, thereby reducing loss of product’s quality. The purpose of the paper is to identify possible loss of quality in the stages of the product’s life cycle through the functions’ modeling of product’s quality. The authors carried out the functions’ modeling of product’s quality based on QFD methodology taking into account existing production, technological and material resources of the enterprise, allowing to formulate the condition for structuring of the quality functions and to increase the degree of the consumer’s satisfaction. This article is intended for top-managers, quality service’s employees of industrial enterprises, researchers interested in the development of the quality management system of industrial enterprise. Keywords: industrial enterprise, quality management system, product quality, modeling, "the vote of the customer" JEL Classifications: Ð¡32, Ð¡52, D11, D12